Family ties and written multilingual heritage of the Frankapani at the dawn of the early modern period - Jurković, Ivan, povjesničar (2020)
In the second half of the fifteenth and the first half of the sixteenth century the Frankapani of Krk, Senj, and Modruš were at the peak of their power. This family of Croatian counts was networked through marriage from the Adriatic to the Baltic Sea with Italian, Hungarian, Austrian, and German royal and aristocratic families. Their presence in the courts of their next of kin, as well as their in-laws, is therefore not surprising, whether it be the Roman Curia or the Hohenzollern Branderburger Palace in Berlin. In such a wide system of communications, the Frankapani presented themselves to the European public as a multilingual family ready to promulgate not only the written heritage nurtured during the Middle Ages in Croatia (Latin and Glagolitic), but also ready to adopt, promote, and disseminate the written heritage of their spouses (Italian, German, Hungarian). The following examples attest to this statement: the Roman breviary translated into the German language by Christopher Frankapan and his wife Apollonia Lang printed in 1518 in Venice, the anti-Turkish speech in Latin delivered by Christopher’s father, Bernardin, before the German assembly in Nuremberg and printed in 1522 for the occasion, the translated epistles of Saint Paul, from Latin to Hungarian, donated by Catherine Frankapan married to Gabriel (Gábor) Perényi, printed in Krakow in 1533, and the first Croatian- language breviary written in the Latin script, rather than in the Glagolitic, commissioned by Catherine Frankapan married to Nicholas Zrinski, published in 1560 in Padua.
Druga je polovica 15. i prva polovica 16. stoljeća razdoblje vrhunca moći Frankapana Krčkih, Senjskih i Modruških. Ta je hrvatska grofovska obitelj bračnim vezama bila umrežena od Jadrana do Baltika s talijanskim, ugarskim, austrijskim i njemačkim vladarskim i velikaškim obiteljima. Ne čudi stoga njihova nazočnost na dvorovima moćnika koji su im bili u prvom koljenu srodstva, ali isto tako i na dvorovima zajedničke im svojte, počevši od Rimske kurije pa do dvora Hohenzollerna Brandenburških u Berlinu. U takvom se širokom sustavu veza Frankapani predstavljaju europskoj javnosti kao multilingvalna obitelj spremna na širenje ne samo pisane baštine njegovane tijekom srednjeg vijeka u Hrvatskoj (latinske i glagoljaške), već i na usvajanje, promoviranje i širenje pisane baštine svojih supružnika (talijanske, njemačke, mađarske). Tomu svjedoče primjerice Rimski brevijar preveden na njemački jezik Krste Frankapana i supruge mu Apolonije Lang otisnut 1518. god. u Veneciji, protuturski govor na latinskom jeziku Krstina oca Bernardina pred njemačkim staležima otisnut 1522. god. u Nürnbergu, doniranje prijevoda s latinskoga na mađarski jezik poslanica sv. Pavla Katarine Frankapan udane za Gabrijela (Gábora) Perényija, koji je i tiskan u Krakovu 1533. god. te prvi časoslov otisnut latiničkim, a ne glagoljskim slovima na hrvatskom jeziku Katarine Frankapan udane za Nikolu Zrinskog, objavljen 1560. god. u Padovi.
Bibliografske bilješke uz tekst ; bibliografija: str. 219-225.
Summary ; Sažetak.
Keywords: Rimski brevijar; Pisana baština -- Prijevodi; Obitelj Frankopan; 16. st